Hfr formation by I pilus-determining plasmids in Escherichia coli K-12. - Datta, N (1976)
R483, an atypical, I pilus-determining plasmid, and also R144, a typical one, were shown to suppress the DnaA phenotype by integration into the Escherichia coli chromosome.